Analytical model for tensile membrane action in RC beam-slab structures under internal column removal - Pham, Anh Tuan (2021)
An analytical approach was developed at Nanyang Technological University, Singapore, to predict structural capacities of RC beam-slab structures under the internal column removal scenario, taking into account the contribution of tensile membrane action in the slab. The model considers both commonly used loading methods in the laboratory, namely, concentrated and uniformly distributed loads. Catenary action in internal beams is neglected for conservatism, and tensile membrane action is assumed to rely solely on the yielding force of the top reinforcement arranged along negative yielding lines in the slab. The failure criterion of the model is based on fracture of longitudinal bars in internal beams, either near the middle or near the edge of beam-column joints. The proposed approach is shown to be reasonable because it provides conservative estimates compared with actual tests, which had high rotational restraints at the slab perimeter, and still gives good predictions for cases of semirigid rotational restraints.